Polychlorinated environmental toxicants affect sphingolipid metabolism during neurogenesis in vitro. (November 2021) - Slováčková, Jana; Slavík, Josef; Kulich, Pavel; Večeřa, Josef; Kováč, Ondrej; Paculová, Hana; Straková, Nicol; Fedr, Radek; Silva, João Pedro; Carvalho, Félix; Machala, Miroslav; Procházková, Jiřina
Graphical abstract: Abstract: Sphingolipids (SLs) are important signaling molecules and functional components of cellular membranes. Although SLs are known as crucial regulators of neural cell physiology and differentiation, modulations of SLs by environmental neurotoxicants in neural cells and their neuronal progeny have not yet been explored. In this study, we used in vitro models of differentiated neuron-like cells, which were repeatedly exposed during differentiation to model environmental toxicants, and we analyzed changes in sphingolipidome, cellular morphology and gene expression related to SL metabolism or neuronal differentiation. We compared these data with the results obtained in undifferentiated neural cells with progenitor-like features. As model polychlorinated organic pollutants, we used 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD), 3, 3′-dichlorobiphenyl (PCB11) and 2, 2′, 4, 4′, 5, 5′-hexachlorobiphenyl (PCB153). PCB153 revealed itself as the most prominent deregulator of SL metabolism and as potent toxicant during early phases of in vitro neurogenesis. TCDD exerted only minor changes in the levels of analysed lipid species, however, it significantly changed the rate of pro-neuronal differentiation and deregulated expression of neuronal markers during neurogenesis. PCB11 acted as a potent disruptor of in vitro neurogenesis, which induced significant alterations in SL metabolism and cellular morphology in both differentiated neuron-like models (differentiated NE4C and NG108-15 cells). We identified ceramide-1-phosphate, lactosylceramides and several glycosphingolipids to be the most sensitive SL species to exposure to polychlorinated pollutants. Additionally, we identified deregulation of several genes related to SL metabolism, which may be explored in future as potential markers of developmental neurotoxicity.